Greece : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Greece. (IMF Staff Country Reports; Country Report ;, 2022)
Greece has weathered the pandemic well, with a considerably stronger-than-expected recovery. Reforms progressed in several areas, including digitalization, privatization, improving the fiscal policy mix, and bank balance sheet repair. Greece finalized its early repayment to the IMF on April 4 and is expected to graduate from the quarterly European Institutions' Enhanced Surveillance framework on schedule by August 2022. Despite the adverse impact of the war in Ukraine, growth is projected to remain robust at 3.5 percent this year. High energy prices are expected to push up average inflation to 6.1 percent. Public debt is on a downward trajectory and rollover risks appear manageable. The external position last year was moderately weaker than that consistent with fundamentals and desirable policies.